Non-Targeted Metabolomic Analysis of Methanolic Extracts of Wild-Simulated and Field-Grown American Ginseng - Lin, Hongqiang (Molecules, 2019)
Aiming at revealing the structural diversity of secondary metabolites and the different patterns in wild-simulated American ginseng (WsAG) and field-grown American ginseng (FgAG), a comprehensive and unique phytochemical profile study was carried out. In the screening analysis, a total of 121 shared compounds were characterized in FgAG and WsAG, respectively. The results showed that both of these two kinds of American ginseng were rich in natural components, and were similar in terms of the kinds of compound they contained. Furthermore, in non-targeted metabolomic analysis, when taking the contents of the constituents into account, it was found that there indeed existed quite a difference between FgAG and WsAG, and 22 robust known biomarkers enabling the differentiation were discovered. For WsAG, there were 12 potential biomarkers including two ocotillol-type saponins, two steroids, six damarane-type saponins, one oleanane-type saponins and one other compound. On the other hand, for FgAG, there were 10 potential biomarkers including two organic acids, six damarane-type saponins, one oleanane-type saponin, and one ursane. In a word, this study illustrated the similarities and differences between FgAG and WsAG, and provides a basis for explaining the effect of different growth environments on secondary metabolites.